1978
DOI: 10.1172/jci109190
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor-Cell Dysfunction in Systemic Lupus Erythematosus

Abstract: A B S T R A C T

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
34
0
2

Year Published

1980
1980
1989
1989

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(40 citation statements)
references
References 26 publications
4
34
0
2
Order By: Relevance
“…Earlier studies demonstrated that patients with active SLE had a loss of suppressor T lymphocyte function (22)(23)(24)(25)(26)(27)(28). Several studies have emphasized the importance of anti-T cell antibodies in altering T cell number and function in patients with active SLE (7,8,(28)(29)(30)(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies demonstrated that patients with active SLE had a loss of suppressor T lymphocyte function (22)(23)(24)(25)(26)(27)(28). Several studies have emphasized the importance of anti-T cell antibodies in altering T cell number and function in patients with active SLE (7,8,(28)(29)(30)(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have used different methods both for the induction of the suppressor cell activity in vitro as well as for the detection and quantitation of suppressor function. Indeed, not all of these reports have dealt with the suppression of T cells on B cells (1,(4)(5)(6)(7)9) or studied its effect on immuno- …”
mentioning
confidence: 99%
“…globulin secreting cells or immunoglobulin production (1,(5)(6)(7)9). An alteration of T cell suppression on immunoglobulin secretion may explain the production of autoantibodies, a characteristic of SLE.…”
mentioning
confidence: 99%
“…The suppression was no different from that (23,24) as well as T-cell subsets determined by a number of other methodologies (25)(26)(27)(28)(29). This is of particular relevance in light of the fact that in several in vitro systems, SLE has been demonstrated to manifest a deficiency of suppressor cell function (23,(30)(31)(32)(33)(34)(35). Although the actual suppressor cell in most of these systems has not been conclusively identified, at least in some systems of in vitro B-cell function, the TG cell has been demonstrated to be the suppressor cell (16).…”
Section: Resultsmentioning
confidence: 66%